Design methodology and simulation study of a FEL amplifier - Gopal, Ram; Jain, Pradip Kumar (International Journal of Engineering and Technology, 2018)
In this paper, the operating behavior and optimization in the TM01 mode of an free electron laser amplifier (FELA) has been discussed using the eigen mode analysis and the simulation techniques and their results has been also analyzed with 3-D particle-in-cell (PIC) codes â€œCST particle studioâ€. To understand the performance analysis and sensitivity of the FEL amplifier using an intense relativistic electron beams (REBs) on various parameter effects such as power, gain, efficiency, beam current, beam voltage and operating frequencies has been explained. In the modeling of an FEL amplifier, the pattern of the magnetic and electric field in TM01 mode has been showed and performed their RF simulation results in the absent case of electron beams i.e., the cold simulation. The reading of the measurement values has been showed for the large radiation growth rate 2dB/cm approximately with 231 GHz instantaneous band width. The good agreement of the simulation results has been found as reported experimental values with predicted theory of operation in the Collective Raman Regime. Additionally, the result to extraction of the kinetic energy from the electron beams to beat-wave has been observed the power and efficiency largely increases experimentally with the linear tapering of the strong axial magnetic field that produces 20% experimental efficiency in the FEL amplifier.